2016
DOI: 10.1007/s12671-016-0568-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Self-compassion as Unique and Common Predictors of Affect in the General Population

Abstract: In contrast to the increased research interest in the benefits of mindfulness and self-compassion, relatively few studies have examined their unique and combined effects in predicting affect. This cross-sectional study examined the predictive value of mindfulness and self-compassion for depressive symptoms, negative affect, and positive affect in a large representative sample of community adults (N = 1736). The Five Facets of Mindfulness Questionnaire (FFMQ) was used as a measure of mindfulness and the Self-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 37 publications
8
21
0
1
Order By: Relevance
“…Bivariate correlations revealed that self-compassion and the five facets of mindfulness measured by the FFMQ were significantly and positively correlated, with the strongest associations found for the facets Nonreact, Act with Awareness, and Nonjudge. Our findings concur with previous research in community samples that showed trait self-compassion and mindfulness are overlapping yet distinct constructs (Birnie et al, 2010;Hollis-Walker & Colosimo, 2011;López et al, 2016), and provide unique data on the connection between these two constructs in individuals with SAD. Intercorrelations between self-compassion, mindfulness and baseline clinical variables indicate that self-compassion and facets of mindfulness influence variation in severity of SAD symptoms and other characteristics of the disorder.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Bivariate correlations revealed that self-compassion and the five facets of mindfulness measured by the FFMQ were significantly and positively correlated, with the strongest associations found for the facets Nonreact, Act with Awareness, and Nonjudge. Our findings concur with previous research in community samples that showed trait self-compassion and mindfulness are overlapping yet distinct constructs (Birnie et al, 2010;Hollis-Walker & Colosimo, 2011;López et al, 2016), and provide unique data on the connection between these two constructs in individuals with SAD. Intercorrelations between self-compassion, mindfulness and baseline clinical variables indicate that self-compassion and facets of mindfulness influence variation in severity of SAD symptoms and other characteristics of the disorder.…”
Section: Discussionsupporting
confidence: 91%
“…The strongest associations were between the FFMQ facet Act with Awareness, which denotes the ability to pay attention in the present moment and avoid automatic pilot, and depression severity (r=-.51), self-esteem (r=.49) and social adjustment (r=-.40). The moderately strong negative association between Act with Awareness and depression is consistent with previous work that showed this specific mindfulness skill may be especially relevant for depression (Baer et al, 2006;Cash & Whitingham, 2010;Curtiss & Klemanski, 2014;López et al, 2016;Royuela-Colomer & Calvete, 2016), possibly because it facilitates disengagement from dysphoric mood and cognitions and engagement in adaptive self-regulatory processes and behaviours. This mindfulness skill may also be relevant to self-esteem and social adjustment through similar mechanisms.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result has also been confirmed by empirical data showing that while the compassionate SCS components of self-kindness, common humanity, and mindfulness are connected to adaptive personality features (e.g., optimism), positive mood states (e.g., happiness), and aspects of well-being (e.g., quality of life), their uncompassionate counterparts of self-judgment, isolation, and over-identification are more clearly linked to negative affect and symptoms of anxiety and depression (e.g., Neff et al 2018a). Thus, the SCS contains multiple dimensions that are differentially related to external constructs (see also Brenner et al 2017Brenner et al , 2018Lopez et al 2015Lopez et al , 2016Muris et al 2018Muris et al , 2019a. It is clear that this has important consequences when researchers use and only report the total score of such a measure as one cannot know the nature of the different dimensions' contributions to that score as well as their unique predictive value for external variables (Smith et al 2009).…”
Section: Critique On the Scsmentioning
confidence: 99%